2017
DOI: 10.21037/jtd.2017.10.149
|View full text |Cite
|
Sign up to set email alerts
|

Does oxygen therapy increase the resolution rate of primary spontaneous pneumothorax?

Abstract: Background: Patients with small pneumothoraces are usually treated with oxygen therapy. However, evidence that oxygen therapy increases resolution rate is based on small populations with secondary spontaneous pneumothorax. Therefore, this study aimed to confirm whether oxygen therapy increases the resolution rate of primary spontaneous pneumothorax (PSP). Conclusions: Oxygen therapy increases the resolution rate of PSP. However, routine use of oxygen therapy in patients with small pneumothoraces should be cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 17 publications
0
21
0
2
Order By: Relevance
“…Patients receiving oxygen had a radiographic resolution rate twice that of those receiving room air (4.3%/day vs 2.1%/day). 59 Although the administration of oxygen may hasten absorption of air from the pleural space, there remains uncertainty regarding the optimal fraction of inspired oxygen, especially the amount that speeds recovery without prolonging hospitalization.…”
Section: Oxygenmentioning
confidence: 99%
“…Patients receiving oxygen had a radiographic resolution rate twice that of those receiving room air (4.3%/day vs 2.1%/day). 59 Although the administration of oxygen may hasten absorption of air from the pleural space, there remains uncertainty regarding the optimal fraction of inspired oxygen, especially the amount that speeds recovery without prolonging hospitalization.…”
Section: Oxygenmentioning
confidence: 99%
“…A small clinical study around the 1970s revealed that adults administered 100% supplemental oxygen therapy demonstrated a fourfold increase in the mean absorption rate [ 21 ]. In an observational study, PSP patients aged approximately 19 years benefited from oxygen therapy, which increased the PSP resolution rate [ 22 ]. However, for neonates, the use of 100% oxygen in pneumothorax treatment indicated little to no advantage compared with the use of room air alone [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[37] One study found a rate of resolution of 4.27% per day with supplemental oxygen compared with 2.06% per day without. [38] As early as 1966, Stradling and Poole [39] published a large series of patients who were managed conservatively and found that only 25% of all spontaneous pneumothoraces needed any form of active intervention. In the group without underlying lung disease, 80% expanded without any intervention, with a mean expansion time of 22.5 days and the mean expansion time was 30.8 days without any intervention in the group with underlying emphysema.…”
Section: Rethinking Intercostal Drain Usementioning
confidence: 99%
“… [37] One study found a rate of resolution of 4.27% per day with supplemental oxygen compared with 2.06% per day without. [38] …”
Section: Management Of a Spontaneous Pneumothoraxmentioning
confidence: 99%